A Review on Pharmacy Practice in South Africa—A Higher Education Perspective - Thokozile Mosiane; Kalaba Nkonde; Gauda Mahlatsi; Nontobeko P. Mncwangi (Pharmacy, 2022)
In April 1994, South Africa underwent the most significant change in its recent history with the disbandment of the policy of apartheid and the attendant race-based politics, which affected most aspects of the country and, of relevance to this review, the education, health delivery, and career choices that race groups could pursue. In the past 28 years, the South African government has tried to implement policies in order to advance political and socioeconomic shifts toward a more equitable society. The healthcare sector was an early target for transformation that was aimed at increasing access to services and the expansion of primary healthcare and hospital facilities to previously underserved areas. This paper seeks to discuss these changes in broad terms, but with specific reference to general health care and pharmacy practice in particular. It will look at the changes in the legislative framework and pharmacy education and factors impacting the pharmacy practices in South Africa over the past 28 years. A discussion of the critical issues that have affected the profession in the last three decades will also be delineated, and future prospects for the profession as a whole, in terms of pharmacy practice and perspectives, will be discussed. We review the current aspects of the pharmacy profession in South Africa today and how the education of those future professionals is a major contribution to the pharmaceutical climate.